Catalytic Effect of Titanium Ions on the Cathodic Reduction of Selenium (VI), Copper (II), Uranium (VI) Ions and Other Metals in an Aqueous Solutions - Bayeshov, Abduali; Bayeshova, Azhar K.; Turlybekova, Makpal N. (EURASIAN JOURNAL OF CHEMISTRY, 2024)
It is known that catalytic processes are widely applied in the field of organic chemistry; however they also play a significant role in inorganic chemistry. Nonetheless, numerous unresolved issues persist in the technology of inorganic substances and the extraction of metals and nonmetals in their elemental states. This publication aims to consolidate the results of our pioneering research utilizing the redox Ti (IV)–Ti (III) system, which demonstrates a catalytic action on the cathodic reduction of selenium (VI), copper (II), platinum (IV), palladium (IV), bismuth, arsenic (V) ions, uranium (VI), as well as manganese dioxide suspension. It has been demonstrated that in the presence of the redox Ti (IV)–Ti (III) system, hard-to-reduce selenate ions can be reduced at room temperature. The catalytic action of the redox Ti (IV)–Ti (III) system has been reliably demonstrated, and the reaction mechanism has been established. In the electrochemical production of metal powders (Cu, Pt, Pd, Bi) at cathode current densities exceeding the limiting value, a portion of the current is irreversibly lost to the discharge of hydrogen ions. Consequently, the current efficiency (CE) for powder production does not exceed 80 %. We have established that in the presence of titanium (IV) ions, due to their catalytic action, the CE increases by more than 15 %. It has also been shown that during the cathodic polarization of hexavalent uranium its reduction to uranium (IV) in the presence of the catalyst increases by more than 50 %. The reduction of hard-to-reduce arsenate ions in the presence of titanium (IV) ions proceeds with high CE to the active trivalent state, and further reduction can proceed electrochemically. The cathodic reduction of a manganese dioxide suspension was investigated. In the presence of a catalyst — titanium (IV) ions, manganese in this dioxide is reduced to the divalent state with a current efficiency exceeding 90 %.